A review of ZnO nanoparticles as solar photocatalysts: Synthesis, mechanisms and applications. (January 2018) - Ong, Chin Boon; Ng, Law Yong; Mohammad, Abdul Wahab
Abstract: Persistent organic pollutants (POPs) are carbon-based chemical substances that are resistant to environmental degradation and may not be completely removed through treatment processes. Their persistence can contribute to adverse health impacts on wild-life and human beings. Thus, the solar photocatalysis process has received increasing attention due to its great potential as a green and eco-friendly process for the elimination of POPs to increase the security of clean water. In this context, ZnO nanostructures have been shown to be prominent photocatalyst candidates to be used in photodegradation owing to the facts that they are low-cost, non-toxic and more efficient in the absorption across a large fraction of the solar spectrum compared to TiO2 . There are several aspects, however, need to be taken into consideration for further development. The purpose of this paper is to review the photo-degradation mechanisms of POPs and the recent progress in ZnO nanostructured fabrication methods including doping, heterojunction and modification techniques as well as improvements of ZnO as a photocatalyst. The second objective of this review is to evaluate the immobilization of photocatalyst and suspension systems while looking into their future challenges and prospects.